2007
DOI: 10.1093/gerona/62.10.1127
|View full text |Cite
|
Sign up to set email alerts
|

Does Functional Recovery in Elderly Hip Fracture Patients Differ Between Patients Admitted From Long-Term Care and the Community?

Abstract: Following hip fracture, most LTC residents do not regain prefracture function irrespective of known prognostic factors. Further investigation is needed as to the extent to which personal and environmental characteristics contribute to outcome after hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 35 publications
4
92
0
3
Order By: Relevance
“…At 6 months post-fracture, a greater proportion of those living in the community before the fracture recovered their pre-fracture function, in comparison to those living in long term care (Table 4 p < 0.001) [48]. The adjusted reduction in pre-fracture function at 6 months was 33 % (95 % CI −40.6 to −27.2) for those in long-term care, and 12 % (95 % CI −14.8 to −8.4) for those community dwelling before the fracture [48]. It should be noted that the pre-fracture mobility of the people in all of these studies was determined retrospectively, so there is a risk of bias in these data.…”
Section: Composite Measures Of Basic Activities Of Daily Livingmentioning
confidence: 99%
See 3 more Smart Citations
“…At 6 months post-fracture, a greater proportion of those living in the community before the fracture recovered their pre-fracture function, in comparison to those living in long term care (Table 4 p < 0.001) [48]. The adjusted reduction in pre-fracture function at 6 months was 33 % (95 % CI −40.6 to −27.2) for those in long-term care, and 12 % (95 % CI −14.8 to −8.4) for those community dwelling before the fracture [48]. It should be noted that the pre-fracture mobility of the people in all of these studies was determined retrospectively, so there is a risk of bias in these data.…”
Section: Composite Measures Of Basic Activities Of Daily Livingmentioning
confidence: 99%
“…Four articles on three cohorts reported functional outcomes for people in residential care [28,[48][49][50]. Canadian and Australian studies have found that recovery of mobility is lower for those living in residential care than for those living in the community (Table 4; Additional file 1: Table S3) [48,49].…”
Section: Activity Outcomes Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals living in nursing homes (or other long-term care settings) are at high risk for hip fractures, such that even after adjustment for confounding factors (including cognitive impairment and chronic illness) their risk remains at least twice that of older adults living in the community [2]. Further, individuals living in long-term care (LTC) are less likely to recover function after a hip fracture than community-living individuals [3]. The costs of hip fracture also vary according to the place of residence.…”
Section: Introductionmentioning
confidence: 99%